Gambaran Pengetahuan Wanita Tentang Menopause Di Dukuh Sorobaon Kelurahan Jati Kecamatan Jaten Kabupaten Karangayar - Rakkuea, Sasitorn; , Winarsih Nur A., S. Kep., NS, ETN., M. Kep (2016)
Menopause is the end of the biological process of menstruation, which is due to the decrease of estrogen produced by the ovaries. The level of knowledge of women about menopause will help women to prepare and can behave and act appropriately in doing the prevention of disturbances that accompany menopause appear. This study aims to describe the knowledge of women about menopause in Sorobaon hamlet Jati village Jaten district Karangayar city. This type of research is descriptive quantitative with cross sectional approach. Sampling using accidental sampling obtained 37 female respondents aged 45-55 years. The results of research were collected using a questionnaire obtained as much as 21 respondents (61,8%) the level of knowledge in the poor category, then quite as much as 10 respondents (29,4%), and well as 3 respondents (8,8%). The level of knowledge of women about menopause in Sorobaon hamlet Jati village Jaten district Karangayar city included in the poor category, because the respondents still lack knowledge about menopause, it is advisable for women to increase their knowledge about menopause by seeking information from the print media, electronic and attend counseling given by health personnel.